Land reform and child health in the Kyrgyz Republic - Kosec, Katrina; Shemyakina, Olga (World Bank, 2019)
Does privatizing land improve child health and nutrition outcomes? We exploit a natural experiment in The Kyrgyz Republic following the collapse of socialism whereby the government rapidly liquidated state and collective farms containing 75 percent of agricultural land and distributed it to individuals, providing 99-year transferrable use rights. We use household surveys collected before, during, and after the reform and data on the spatial variation in the timing of privatization to identify its health and nutrition impacts. We find that children exposed to land privatization for longer periods of time accumulated significantly greater gains in height and weight, both critical measures of long-term health and nutrition. Children who benefited most from privatization were between the ages of 1 and 1.5—possibly due to protective effects of breastfeeding for children younger than a year old, and reduced vulnerability to health shocks at older ages. We find no evidence of significant gender differences in the effects of privatization.